One fish, two fish, red fish, blue fish. - Seuss, Dr. (New York : Beginner Books; distributed by Random House, 1960)
A story-poem about the activities of such unusual animals as the Nook, Wump, Yink, Yop, Gack, and the Zeds.
K-3
270L
L
1.2
Keywords: Stories in rhyme; Fantasy; Nonsense verses; Readers (Elementary)